Panaxydol attenuates ferroptosis against LPS-induced acute lung injury in mice by Keap1-Nrf2/HO-1 pathway - Li, Jiucui; Lu, Kongmiao; Sun, Fenglan; Tan, Shanjuan; Zhang, Xiao; Sheng, Wei; Hao, Wanming; Liu, Min; Lv, Weihong; Han, Wei (Journal of translational medicine, 2021)
Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) induces uncontrolled and self-amplified pulmonary inflammation, and has high morbidity and mortality rates in critically ill patients. In recent years, many bioactive ingredients extracted from herbs have been reported to effectively ameliorate ALI/ARDS via different mechanisms. Ferroptosis, categorized as regulated necrosis, is more immunogenic than apoptosis and contributes to the progression of ALI. In this study, we examined the impact of panaxydol (PX), isolated from the roots of Panax ginseng, on lipopolysaccharide (LPS)-induced ALI in mice. In vivo, the role of PX on LPS-induced ALI in mice was tested by determination of LPS-induced pulmonary inflammation, pulmonary edema and ferroptosis. In vitro, BEAS-2B cells were used to investigate the molecular mechanisms by which PX functions via determination of inflammation, ferroptosis and their relationship. Administration of PX protected mice against LPS-induced ALI, including significantly ameliorated lung pathological changes, and decreased the extent of lung edema, inflammation, and ferroptosis. In vitro, PX inhibited LPS-induced ferroptosis and inflammation in bronchial epithelial cell line BEAS-2B cells. The relationship between ferroptosis and inflammation was investigated. The results showed that ferroptosis mediated inflammation in LPS-treated BEAS-2B cells, and PX might ameliorate LPS-induced inflammation via inhibiting ferroptosis. Meanwhile, PX could upregulate Keap1-Nrf2/HO-1 pathway, and selective inhibition of Keap1-Nrf2/HO-1 pathway significantly abolished the anti-ferroptotic and anti-inflammatory functions of PX in LPS-treated cells. PX attenuates ferroptosis against LPS-induced ALI via Keap1-Nrf2/HO-1 pathway, and is a promising novel therapeutic candidate for ALI.